Critical Issues On Learning Process Amidst Covid-19 Perceived From Pedagogical Perspectives - Maximus Gorky Sembiring (LPPM Universitas Terbuka, 2022)
This study examined the implementation of online learning that took place during the Covid-19 pandemic. The goal was to unravel and straighten out various doubts and complaints in the community who think that the implementation of online learning caused problems rather than an alternative to the practical mode of learning. The study utilized a literature study (library research), that is integrative review. It was closely related to the semi-structured review aiming at assessing, criticizing, and synthesizing the literature on the related research topic in a way that enables new theoretical frameworks and perspectives to emerge. Additionally, the process follows four phases: design, conduct, analysis, and finally structuring and writing the review. The study showed a broad misunderstanding in society about what happened during working and studying from the home period. Many people suspected that what happened was online learning. However, it is not online learning but an emergency remote teaching instead. This implied that most online learning in operations did not meet the standardized requirements as it was established. Furthermore, not using the intelligent flexible learning model (the Fifth Generation of Online Learning Mode) resulted in significant complications at the operational level. Moreover, what factually happened did not meet the characteristics of online learning systems and services. Above all, most online learning institutions still ignore the use of appropriate pedagogics. This study also demonstrated the importance of utilizing a complete instructional design so that the learning experience as a condition for the learning outcomes effectively achieved was equally present in the learning process. Comprehensive planning that was arranged systematically and structured will allow dialogue for students in the implementation stage. The dialogue space must occur not only between students and teachers as well as students and students but also, more importantly, self-dialogue for each student. Some insights for future consideration were also formulated and recommended for better online learning implementation